City and ocean: journeys, memory, imagination - White, Jonathan (ed.); Wang, I-Chun (ed.) (Newcastle, 2012)
Throughout history cities have been locations of human encounter. Equally they have been contexts for the trade of goods and services, for the evolution of various forms of urban space, and for the production, development, and enrichment of culture and technology. Many cities grew up along shorelines, which themselves constitute some of the globe's most important cultural boundaries. For above all else, it is water that has separated but also connected different communities, races, religions and nations, down through recorded time. With the rapid advance in technologies of communication, encounters between cultures have multiplied at a rate that no individual can follow or control. The present book constitutes a space of memory in its own right, one of its chief raisons d'etre being that a group of diverse scholars herein maps certain key encounters between people, past as well as present, and the urgent issues generated in consequence. No one person could have traced such diversity and made sense of it, whereas a scholarly grouping of persons reporting on phenomena from around the world, such as is provided here, offers its readers a vision of global change and development. With the twentieth and twenty-first centuries a new set of mega-cities in Asia, Africa, and Latin America has emerged to challenge the primacy of European and North American metropolitan centres. This expanded landscape is here interpreted with special attention, as already mentioned, to cities located at coastlines, hence (generally speaking) more exposed to globalizing trends. Migrants, exiles and refugees, ethnic and racial minorities, as well as alternative or countercultural groupings continue to complicate the ways in which cities articulate their now pluralized identities, in terms of (and by means of) literature, history, architecture, social events, and other forms of artistic and cultural production. The international scholars whose work is assembled in these pages are well placed to engage with the intersecting themes and issues of the volume. Contributors have mapped different examples from Homeric narrative, through Renaissance drama and its representation of crossways of culture such as Rhodes and Malta, to an earlier time in the development of a New World city such as Boston: others look at the twentieth and twenty-first centuries' complexity of great world cities and of oceanic migration or trade between them. Shanghai, Singapore, London, Detroit, Shantou, Macau, and Saigon are some that are dealt with in detail. Emphasis falls on both the historical reality of those contexts as well as how they have been culturally represented.
Keywords: Cities and towns-Social aspects